Barriers to implementing an oral care regime for patients with dysphagia - Tiwari, Akhilesh; Daniel, Vivek (Jour Med Resh and Health Sci, 2020)
Elderly hospitalised patients with dysphagia are at an increased risk of respiratory complications, including aspiration pneumonia. Evidence suggests that oral hygiene regimes can reduce this risk. Despite this, oral care provision in acute hospitals is variable and particularly limited in elderly care settings. This literature review explores the barriers to implementation of oral care, including lack of evidence-based protocols and inadequate accountability structures within organisations, reduced staff knowledge, staff attitudes and beliefs, as well as patient-related factors such as non-compliance. Organisational factors emerge as an important theme and require further research in order to improve outcomes for this vulnerable population.